ON MENELAUS' SPHERICS III.5 IN ARABIC MATHEMATICS, I: IBN ʿIRĀQ. Issue 1 (24th January 2014) - Rashed, Roshdi; Papadopoulos, Athanase
Abstract: This is the first paper in a series in which we provide critical editions of four texts written between the eleventh and the thirteenth century concerning Proposition III.5 of Menelaus' Spherics . The first paper contains introductory material on the work of Ibn ʿIrāq on spherical geometry and a critical edition of his two texts on the rectification of Proposition III.5, together with translations and historical and mathematical commentaries. The second paper contains critical editions of the texts by Naṣīr al-Dīn al-Ṭūsī and Ibn Abī Jarrāda on the same subject, again with translations and historical and mathematical commentaries. Résumé: C'est le premier d'une série d'articles comportant quatre textes composés entre le XI e et le XIII e siècle, qui traitent de la proposition 5 du livre III des Sphériques de Ménélaüs. Le premier article comprend des commentaires historiques et mathématiques de l'œuvre d'Ibn ʿIrāq en géométrie sphérique et une édition critique des deux textes qu'il a consacrés à la rectification de la proposition III.5, ainsi que la traduction de ces deux textes. Le second article propose une édition critique des textes de Naṣīr al-Dīn al-Ṭūsī et d'Ibn Abī Jarrāda sur le même sujet, cette fois aussi avec une traduction et des commentaires historiques et mathématiques.